Pressurized Ammonia and Syngas Planar Anode-Supported Solid Oxide Fuel Cells and Their Performance Stability Test. (10th July 2019) - Shy, Shenqyang Steven; Hung, Y. T.; Chou, Z. H.; Bong, Z. L.; Jhao, J. J.
Abstract : This paper reports a stability test comparison between ammonia- and syngas-fueled anode-supported cells (ASC). The planar (50 x 50 mm 2 ) ASC is consisted of 400-mm-Ni-YSZ anode, 3-mm-YSZ electrolyte, and 12-mm-LSC-GDC cathode together with metallic frames and current collectors which are sandwiched by a pair of rib-channel flow distributors (interconnectors) with guide vanes on both anode and cathode sides to form a single-full-cell stack in a dual-chamber pressure/temperature-controlled facility. Pressurization enhances the power density noticeably for both ammonia- and syngas-fueled ASCs. Little degradation is observed for the pressurized ammonia-fueled ASC at 0.8 V at 700°C (power density and stability increase with increasing temperature). However, the syngas-fueled ASC can only remain stable at 1 atm and at higher temperature (≥ 800°C); after five hours stable operation, a rapid degradation is observed at 3 atm due to severe carbon deposition even at 850°C.